Measurement tools for gender identity, gender expression, and gender dysphoria in transgender and gender-diverse children and adolescents: a systematic review. (August 2021) - Bloom, Thea M; Nguyen, Thomas P; Lami, Francesca; Pace, Carmen C; Poulakis, Zeffie; Telfer, Michelle; Taylor, Amelia; Pang, Kenneth C; Tollit, Michelle A
Summary: Increasing numbers of children and adolescents are being referred to gender services for gender-related concerns. Various instruments are used with these patients in clinical care, but their clinical validity, strengths, and limitations have not been systematically reviewed. In this systematic review, we searched MEDLINE, PubMed, and PsycINFO databases for available tools that assess gender identity, gender expression, or gender dysphoria in transgender and gender-diverse (TGD) children and adolescents. We included studies published before Jan 20, 2020, that used tools to assess gender identity, expression, or dysphoria in TGD individuals younger than 18 years. Data were extracted from eligible studies using a standardised form. We found 39 studies that met the inclusion criteria, from which we identified 24 tools. The nature of tools varied considerably and included direct observation, child and adolescent self-report, and parent-report tools. Many methods have only been used with small samples, include outdated content, and lack evaluation of psychometric properties. In summary, a paucity of studies in this area, along with sparse reporting of psychometric properties, made it difficult to compare the relative use of tools, and current tools have substantial limitations. Future research is required to validate existing measures and create more relevant, culturally appropriate tools.